Mesoporous Composite Networks of Linked MnFe2O4 and ZnFe2O4 Nanoparticles as Efficient Photocatalysts for the Reduction of Cr(VI) - Skliri, Euaggelia; Vamvasakis, Ioannis; Papadas, Ioannis T.; Choulis, Stelios A.; Armatas, Gerasimos S. (My University, 2021)
Semiconductor photocatalysis has recently emerged as an effective and eco-friendly approach that could meet the stringent requirements for sustainable environmental remediation. To this end, the fabrication of novel photocatalysts with unique electrochemical properties and high catalytic efficiency is of utmost importance and requires adequate attention. In this work, dual component mesoporous frameworks of spinel ferrite ZnFe2O4 (ZFO) and MnFe2O4 (MFO) nanoparticles are reported as efficient photocatalysts for detoxification of hexavalent chromium (Cr(VI)) and organic pollutants. The as-prepared materials, which are synthesized via a polymer-templated aggregating self-assembly method, consist of a continuous network of linked nanoparticles (ca. 6–7 nm) and exhibit large surface area (up to 91 m2 g−1 ) arising from interstitial voids between the nanoparticles, according to electron microscopy and N2 physisorption measurements. By tuning the composition, MFO-ZFO composite catalyst containing 6 wt.% MFO attains excellent photocatalytic Cr(VI) reduction activity in the presence of phenol. In-depth studies with UV-visible absorption, electrochemical and photoelectrochemical measurements show that the performance enhancement of this catalyst predominantly arises from the suitable band edge positions of constituent nanoparticles that efficiently separates and transports the charge carriers through the interface of the ZFO/MFO junctions. Besides, the open pore structure and large surface area of these ensembled networks also boost the reaction kinetics. The remarkable activity and durability of the MFO-ZFO heterostructures implies the great possibility of implementing these new nanocomposite catalysts into a realistic Cr(VI) detoxification of contaminated wastewater.
Keywords: Zinc ferrite; Manganese ferrite; Mesoporous materials; Nanoparticles; Metal oxides; Electronic band structure; Photocatalysis; Hexavalent chromium; Organic pollutants; Environmental remediation